Quality Management in Academic Medical Education: A Focus on Serbia - Milić, Marko Kimi; Sinanović, Šćepan; Kostić, Dejan; Ralić, Branislav (Medical Gazzette, 2026)
Introduction: This study analysed quality management practices in Serbian vocational higher medical schools, focusing on their alignment with national and international standards and the specific challenges of practically oriented medical education.Methods: A mixed-methods design was applied in five accredited vocational institutions. Quantitative data included accreditation documents, institutional indicators (enrolment, dropout and graduate employment rates), and structured surveys of teaching staff (n = 124) and students (n = 298). Qualitative data were obtained through semi-structured interviews with directors, department heads and quality-assurance coordinators (n = 18), eight student focus groups, and analysis of internal QA policies and strategic plans.Results: Quantitative findings showed moderate overall satisfaction among staff and students, with higher ratings for practical training and curriculum relevance and lower ratings for infrastructure, equipment and assessment transparency. Dropout rates remained relatively low, while graduate employment was generally high. Qualitative data highlighted persistent resource constraints, staff shortages, and uneven adoption of e-learning and simulation technologies. Accreditation was widely perceived as necessary but often approached as a periodic compliance exercise rather than a driver of continuous improvement. Stakeholder feedback mechanisms existed but were inconsistently used, resulting in weak feedback loops.Discussion: Serbian vocational higher medical schools demonstrate resilience and strong practical training despite systemic and financial constraints. Strengthening strategic investment in infrastructure, embedding continuous QA processes into everyday practice, modernising assessment methods and expanding digital and telemedicine-related learning environments are key priorities for enhancing educational quality and healthcare workforce preparedness.
Keywords: Quality assurance, accreditation, vocational medical education, Serbia, practical training, continuous improvement, telemedicine integration, resource allocation.